2012
DOI: 10.1159/000341770
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Ameliorates Endothelial Dysfunction in Those with Impaired Glucose Regulation among the First-Degree Relatives of Type 2 Diabetes Mellitus Patients

Abstract: Objective: To study the effects of pioglitazone on endothelial dysfunction of subjects with impaired glucose regulation (IGR) among the first-degree relatives of patients with type 2 diabetes mellitus (T2DM). Subjects and Methods: The first-degree relatives of T2DM patients were screened with oral glucose test and IGR was diagnosed. IGR subjects whose blood glucose was still above the level after 1-month exercise were randomized to receive pioglitazone (15 mg/day) or vehicle for 12 weeks. Endothelial function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…These modifications were confirmed with the MRI investigation that recorded the highest descending aorta volume ( Figure 7 ). These findings were concordant with the study performed on persons with impaired glucose regulation by Yu et al, which showed the increase in nitric oxide levels after the administration of pioglitazone at a dose of 15 mg/day for 12 weeks [ 28 ]. The vasodilation may be also explained by the opening effect of pioglitazone on the smooth muscle K V (voltage-dependent K + ) and/or KIR (inward rectifier K + ) channels that was reported by Nomura et al in their study on the isolated rat aorta [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…These modifications were confirmed with the MRI investigation that recorded the highest descending aorta volume ( Figure 7 ). These findings were concordant with the study performed on persons with impaired glucose regulation by Yu et al, which showed the increase in nitric oxide levels after the administration of pioglitazone at a dose of 15 mg/day for 12 weeks [ 28 ]. The vasodilation may be also explained by the opening effect of pioglitazone on the smooth muscle K V (voltage-dependent K + ) and/or KIR (inward rectifier K + ) channels that was reported by Nomura et al in their study on the isolated rat aorta [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Collectively, these data strongly suggest that metformin protects the vasculature through mechanisms that are independent of IR. However, a study with another peroxisome proliferator-activated receptor γ ligand, pioglitazone, concluded that this thiazolidinedione did improve both insulin sensitivity and EDV as well as elevating blood levels of NO in patients with impaired glucose regulation [ 120 ].…”
Section: Metformin Vascular Protection and Insulin Resistancementioning
confidence: 99%
“…In the recent randomized, double-blind, and prospective study of Yu et al (2013) [ 17 ], it has been determined that pioglitazone ameliorated ED in subjects with impaired glucose regulation among first-degree relatives of T2DM patients. The test group consisted of 107 first-degree relatives (30–59 years of age) that were diagnosed with impaired glucose regulation or impaired fasting glucose for the first time or before, but without treatment or already off of treatment for more than three months.…”
Section: Pioglitazone-related Findings Obtained On Humansmentioning
confidence: 99%
“…Macroangiopathy, as a pathological condition, is known to be directly correlated with atherosclerosis, which is in turn associated with vascular ED and reduced NO. Diabetic macroangiopathy, with the consequential peripheral vascular disease, stroke, or coronary heart disease, can be marked as the leading cause of mortality and disability due to T2DM [ 17 ]. This is supported by the fact that an accelerated progression of the atherosclerotic process can be detected in patients with T2DM [ 18 ].…”
Section: Introductionmentioning
confidence: 99%